(untitled) (Journal of the Bangladesh Society of Anaesthesiologists, 2019)
Myasthenia Gravis (MG) is an acquired, autoimmune disorder affecting neuromuscular junctionpresenting with easy fatigability, progressive weakness, diplopia, difficulty in speaking and swallowingand even ventilator failure in severe cases. During pregnancy the disease may go into remission or mayexacerbate at any time during first, second and third trimesters or postpartum period. We are reportinga case of a 32 years old primi gravida, a known case of MG, who underwent emergency caesarian sectiondue to postdated pregnancy. Both the mother and the baby were well managed in the perioperative period. JBSA 2019; 32(1): 38-41